2018
DOI: 10.21307/ane-2018-014
|View full text |Cite
|
Sign up to set email alerts
|

Summation of two illusions of extent

Abstract: In the present visual psychophysical study, the Oppel-Kundt and and Müller-Lyer illusion magnitudes were measured separately (by single figures) and in combination (by two patterns superposed spatially). Data for 30 subjects revealed extensive variability both for the separate and combined illusion strength. Nevertheless, the effect of addition of the perceived length distortions was established. The combined illusions were significantly stronger than the separate ones. Dynamics of the misperceptions summation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The individual IO-K functions (Fig. 3) exposed a common non-monotonic profile as well, irrespective of wide dispersion in the illusion strength, which may have primarily been caused by the individual properties of the visual signal processing (Bertulis et al, 2018).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The individual IO-K functions (Fig. 3) exposed a common non-monotonic profile as well, irrespective of wide dispersion in the illusion strength, which may have primarily been caused by the individual properties of the visual signal processing (Bertulis et al, 2018).…”
Section: Methodsmentioning
confidence: 93%
“…Both factors were perceptually significant. Importance of the contours was emphasized during testing of the superposed O-K figures comprising a regular sequence of uniform filling stripes, a contour rectangle, or a solid block (Bertulis et al, 2014), and also in an examination of the expansion effect produced by the Müller-Lyer wings attached to the O-K pattern with either spots or high stripes (Bertulis et al, 2018). The next excitation factor, the filling mode, mattered to the illusion as well.…”
Section: Introductionmentioning
confidence: 99%
“…In both perceptual domains, these illusions have versions where multiple fillers make a continuous perceptual object and are referred to as filled duration (Grondin et al, 2018) and filled space illusions (Bulatov et al, 2017). In visual perception research, it is known that the combined Oppel-Kundt and Müller-Lyer effects enhance or diminish the overall illusion strength (Bertulis et al, 2018). Bulatov et al (2017) suggested the size-estimation process description with a quantitative model, which explains the Oppel-Kundt illusion and in which the centroid extraction is an inherent component.…”
Section: Discussionmentioning
confidence: 99%